Iwacura, Clay County - Hess, Kyle (Kansas State University, The Chapman Center for Rural Studies, 2011)
Before the advent of the automobile, Iwacura arose out of necessity to disperse mail and save souls. James Henry Geist established a post office and the United Brethren Church was built nearby. Both served local farms in the area when it was an inconvenient distance to travel to the larger towns of Idana and Morganville by horse or buggy.
Kyle Hess, “Iwacura, Clay County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/40.
Keywords: Clay County; Idana; Iwacura; James Henry Geist; Kyle Hess; Morganville